Trade, innovation and optimal patent protection - David Hémous; Simon Lepot; Thomas Sampson; Julian Schärer (University of Zurich, Department of Economics, 2024)
Intellectual property rights are a recurrent source of tensions between developed and developing economies. This paper provides the first quantitative analysis of optimal patent policy in trading economies. We develop a new model of trade, growth and patenting in which patent protection affects both innovation and market power. The model is estimated using data on patent applications to calibrate patent protection by country and the geography of innovation. Counterfactual analysis yields three main results. First, the potential gains from international cooperation over patent policies are large. However, achieving these gains requires more innovative economies to offer stronger protection. Second, only a small share of these gains has been realized so far. And third, by pushing towards policy harmonization, the TRIPS agreement hurts developing countries without generating global welfare gains. Overall, there is substantial scope for policy reforms to increase efficiency.
Keywords: F10; F13; F55; O33; O40; 330